Ocadaic acid treatment alters the intracellular localization of caveolin-1 and caveolin-2 in HepG2 cells - L. Kiss, Anna (Acta Biologica Szegediensis, 2003)
In this paper we provide evidences that protein phosphatases could regulate the intracellular localization of caveolin isoforms in a hepatoma cell line (HepG2). Ocadaic acid (OA) - a serine/threonine phosphatase inhibitor – was used in various concentrations (4nM and 100nM) to study the localization of caveolin-1 and caveolin-2 in HepG2 cells. Using fluorescent and confocal immunocytochemistry we have found that OA in both concentrations has significantly altered the intracellular localization and distribution of the caveolin-1 and caveolin-2 as well. In control (-OA treatment) the caveolin-1 was present in discrete punctate structures in the cytoplasm and also on the cell membrane. Caveolin-2 has partly overlapped with caveolin-1, but a significant amount caveolin-2 was detected around the nucleus. After OA (4 and 100 nM) treatment caveolin-1 has disappeared from the cell membrane, it was present mainly in the cytoplasm in larger vesicle or vacuole-like structures that were arranged along the cables of the cytoskeleton. In many cases caveolin-2 was found to colocalize with caveolin-1, but there was always a significant amount of caveolin-2 present around the nucleus. Immunoprecipitation and Western blot analysis revealed that in OA-treated cells a 24 kDa protein identified as caveolin-2 was strongly phosphorylated on tyrosine residues. The effect of OA was not reversible, since the removal of OA has not resulted in the dephosphorylation of caveolin-2 and the perinuclear localization of caveolin-2 remained. Our data indicate that phophorylation of caveolin-2 can alter not only the intracellular localization of caveolin isoforms but also the distribution of caveolae. The cytoskeleton seems to play an important role in the normal and altered distribution of caveolae, and the tyrosine phosphorylation or the absence of dephosphorylation of caveolin-2 isoform can inhibit the recycling of caveolae.